‘Tais’: a new pear cultivar for the Middle Urals - G. N. Tarasova; L. А. Kotov; D. D. Telezhinskiy (Труды по прикладной ботанике, генетике и селекции)
Expanding the assortment through the development of new highly adaptable cultivars is the main task of pear breeding in the Middle Urals. The most significant agronomic traits are winter hardiness, high fruit yield, and good fruit quality. The zoned pear assortment for the Middle Urals includes six cultivars. Six more cultivars now undergo the State Variety Trials. One of them is the new pear cultivar ‘Tais’ (breeding number DL-33-104), the result of crossing Dyuymovochka × Zhanna d’Ark. Cv. ‘Tais’ has been in variety studies at Sverdlovsk Horticultural Breeding Station (Yekaterinburg) since 2006. The new cultivar is characterized by good winter hardiness and productivity. The average yield at the age of 10–14 years is 9.42 tons per hectare, while the maximum yield is 19.81 t/ha. Fruits are yellow, with a good sweet taste, weighing 94 g. The content of dry matter is 11.9%, sugars 9.0%, and titratable acids 0.4%. According to the results of long-term research, the new pear cultivar ‘Tais’ was submitted to the State Variety Trials in 2017.